IMPROVING LOCAL GUIDES’ SPEAKING SKILL TROUGH ROLE PLAY - Hamdan Anwari (Sekolah Tinggi Pariwisata Mataram, 2021)
This research is to face learners’ obstacles in speaking English. Researcher used an approach to teach speaking skill. Role play is strategy done by researcher that can be used to overcome 13 local guides English communication problem. This research belongs to classroom action research that uses the technique to teach speaking to the local guides in Kulon Progo by using role play as activity in learning process. This research needed two cycles that include. That was started by conducting pre-test. There were five steps in conducting action research such as planning, acting, observing, implementing and reflecting in each cycle. Those cycles showed local guides’ improvement in speaking English. Learners also showed their improvement in speaking English that can be seen by five speaking acpects. Five aspects of speaking which well improved such as fluency, dictation, pronunciation, intonation and grammar. The improvement was analized by comparing different score between pre-test and two upcoming cycles. The increase of speaking aspect score was seen from the comparion of pre-test to the cycle 1. It was obtained 3.08. While the obtained score of comparion between cycle 1 and cycle 2 was 5,385. It showed improvement score from each cycle of local guides English communication.